Developing Critical Thinking Skills through Visual Arts Education - Kamolova E’zoza Iskandar qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the role of visual arts education in fostering critical thinking skills among students. It highlights pedagogical strategies, including project-based learning, interactive methods, and interdisciplinary approaches, that encourage analysis, evaluation, and problem-solving. Drawing on the research of Shovdirov S. A., the study demonstrates how integrating these strategies with digital tools enhances students’ creative and cognitive competencies, preparing them for both academic and professional success.